Assessment of Soil Contamination Due to Leaching of Industrial Wastewater - GITIPOUR, SAEID; GIVEHCHI, SAEID; AGHAII, ALIREZA; BAGHVAND, AKBAR (Asian Journal of Chemistry, 2010)
This research has investigated the soil pollution at a lead and zinc contaminated site (Deezaj Abad). For many years the leakings of wastewater generated by National Lead and Zinc Plant (NLZP) has polluted the soil at the site. The study was carried out by conducting toxicity characteristics leaching procedure (TCLP) leach tests and performing lead and zinc analysis on soil and liquid samples to determine the concentration of the metals. Following testing and analysis of the samples, concentrations of lead and zinc in soil and plant's wastewater were compared with TCLP standards, European Union limits (EC-175) and World Health Organization guidelines. By comparing the total analysis results (ranging from 110 to 370 ppm for lead and 540 to 690 ppm for zinc) for the soil samples with the allowable concentrations of 84 and 200 ppm proposed by the above guidelines it could be concluded that the soil at the site was polluted with the heavy metals. Regarding the plant's waste-water, the concentration of the metals exceeded the allowable concentrations of TCLP test and World health Organization limits. At the end of this study, remediation methods for treatment of contaminated soils at the site are proposed.